Application of fragment based virtual screening towards inhibition of bacterial N-acetyglucosaminidase. Issue 9 (2nd September 2018) - Tibaut, T.; Tomašič, T.; Hodnik, V.; Anderluh, M.; Pintar, S.; Novič, M.; Turk, D.
ABSTRACT: A structure-based approach is applied for the development of inhibitors of bacterial N- acetyglucosaminidase (autolysin). Autolysins are enzymes involved in the degradation of peptidoglycan and therefore participate in bacterial cell growth and different lysis phenomena. Several studies indicate that by the inhibition of autolysins, and consequently of bacterial cell division, antibacterial activity can be obtained, thus paving the road to a novel group of therapeutics against human pathogens. As crystal structures of the autolysin E (AtlE)–ligand complexes were obtained in our laboratories, fragment-based virtual screening was the method of choice for the initial studies. Fragment libraries from various databases were merged to increase the number of compounds for the virtual screening. Twenty-four commercially available virtual hits were selected and subjected to quantitative analysis of binding interactions using the surface plasmon resonance technique. Twelve fragments showed fragment–AtlE interactions. For F1, the top hit of the virtual screening, a K D of 228 µM was determined, while other fragments displayed non-stoichiometric binding. Blind docking of potential binders uncovers three possible allosteric sites. Ligands of N- acetyglucosaminidase identified in our study represent valuable information for the further development of AtlE inhibitors, which could in future represent antibacterial agents acting by a novel mode of action.